Fusarium keratoplasticum TKKS-1: A potential native entomopathogenic fungus to control Armyworm, Spodoptera litura Fabricus (Lepidoptera: Noctuidae), on mustard plants - Sahid, Abdul; Akhsan, Ni’matuljannah; Sundari, Fety (Universitas Lampung, 2026)
The use of entomopathogen (insect pathogen) is one of the effective strategies for managing insect pests. This study aimed to evaluate the efficacy of the entomopathogenic fungus Fusarium keratoplasticum against Spodoptera litura larvae under laboratory conditions and to assess its potential in controlling infestations on mustard plants. The pathogenicity of the fungal isolate was tested against third-instar S. litura larvae at a concentration of 1 × 107 conidia/mL. Both fungal isolates caused 100% larval mortality, however, F. keratoplasticum acted more rapidly than Beauveria bassiana, reaching 100% mortality within 6 days, compared to 9 days for B. bassiana. The virulence of F. keratoplasticum was further evaluated using a Simple Completely Randomized Block Design (SCBD) consisting of five treatments with different conidial concentrations (1 × 106, 2 × 106, 4 × 106, 8 × 106, and 1 × 107 conidia/mL) and an untreated control. A commercial B. bassiana formulation (1 × 107 conidia/mL) served as a comparison. The application technique involved direct exposure of S. litura larvae to the fungal suspensions. The LC50 value of F. keratoplasticum was 2.74 × 106 conidial/mL, while the LT50 value at 1 × 107 conidia/mL was 2.96 days, significantly shorter than that of B. bassiana (LT50 = 3.63 days). Under semi-field conditions, F. keratoplasticum demonstrated superior effectiveness in controlling S. litura larvae on mustard plants, achieving complete mortality more rapidly than under laboratory conditions and outperforming B. bassiana. These findings indicate that F. keratoplasticum has strong potential to be developed as a biopesticide.